Use of anticonvulsive drugs during pregnancy and the risk of malformations in the newborn: A meta-analysis (2003)
Objective. To determine the risk, if any, of anticonvulsants use on the foetus with respect to major malformations. Materials and methods. MEDLINE, EMBASE, SCISEARCH and programs as ProQuest, HINARI y Ovid were searched for human studies. Studies that examined the effects of systematic exposure to any anticonvulsant during pregnancy (any dose, any duration, indicated for any type of epilepsy) were eligible. Studies that assessed major malformations in the infants were eligible. Major malformations were defined using the criteria described by Holmes. The number of neonates exposed to anticonvulsants who did and did not exhibit major malformations, and the number of neonates not exposed to anticonvulsants who did and did not exhibit major malformations, were extracted in the form of 2 × 2 tables. The odds ratio (OR), relative risk and 95% confidence interval (CI) was calculated for each of the studies. Results. Ten cohort studies and four case-control studies were included. A total of 2,509 cases and 433,890 controls were included. Major malformations were found in 9,8% among the exposed children and 7,4% among the non exposed. (OR: 2,7; CI 95%: 2.062-3.641; p < 0.000). There was no evidence of an association between any anticonvulsant and a specific major malformation. Conclusions. The available epidemiological data support the hypothesis that anticonvulsants increase the risk of major malformations by an order of 2- to 3-fold.